Technology Advancements in Blood Coagulation Measurements for Point-of-Care Diagnostic Testing - Mohammadi Aria, Mohammad; Erten, Ahmet; Yalcin, Ozlem (Frontiers in Bioengineering and Biotechnology, 2019)
In recent years, blood coagulation monitoring has become crucial to diagnosing causes of hemorrhages, developing anticoagulant drugs, assessing bleeding risk in extensive surgery procedures and dialysis, and investigating the efficacy of hemostatic therapies. In this regard, advanced technologies such as microfluidics, fluorescent microscopy, electrochemical sensing, and photoacoustic detection, and micro/nano electromechanical systems (MEMS/NEMS) have been employed to develop highly accurate, robust, and cost-effective point of care (POC) devices. This devices measuring electrochemical, optical, and mechanical parameters of clotting blood. The parameters could be correlated to light transmission/scattering, electrical impedance, and viscoelastic properties. In this regard, this paper discusses the working principle of blood coagulation monitoring, physical and sensing parameters in different technologies. On the other hand, we discussed the recent progress in developing nanomaterials for blood coagulation detection and treatments which opens up new area of controlling and monitoring of coagulation at the same time in the future. Moreover, commercial products, future trends/challenges in blood coagulation monitoring including novel anticoagulant therapies, multiplexed sensing platforms, and the application of artificial intelligence in diagnosis and monitoring have been included. Key words: blood coagulation, POC devices, electrochemical sensing, MEMS, fluorescent microscopy, microfluidics, nanomaterials, and photoacoustic detection.